INVENTORY CONTROL MANAGEMENT AND REVENUE GENERATING CAPABILITIES OF OIL AND GAS DRILLING FIRMS IN NIGERIA - JOSEPH, Fineboy Ikechi; OMODERO, Cordelia Onyinyechi; OKEZIE, Uzochi Chinkata (Annals of Spiru Haret University. Economic Series, 2019)
Abstract The critical role of effective inventory control has been much emphasized in the oil and gas industry which is subdivided into upstream and downstream sectors with drilling activities falling within the upstream subsector. In light of this development, this study investigates effective inventory control and effective drilling activities of oil and gas drilling firms as well as its relationship with revenue generating capabilities of oil drilling firms in Nigeria. Simple random sampling technique was adopted. Presentation and analyses of primary data collected with questionnaire and testing of the hypotheses were done using percentage and Spearman’s Rank correlation coefficient. The results from the tests with the use SPSS show positive and significant correlation between ineffective inventory management and downtime in the operations of oil and gas drilling with a correlation value of 0.682 with p-value = 0.001< 0.05 which implies that there is 68% relationship between ineffective management and downtime drilling. There is a significant correlation between incessant downtime in operations of oil and gas drilling firms and their income level owing to poorly managed inventory control with a correlation coefficient value of 0.788 with p-value = 0.000< 0.05 which implies that there is 79% relationship between income (profit) level and downtime in drilling operations. Incessant downtime in drilling operations of oil and gas firms as a result of poor inventory control management has significant difference with termination of contract of oil drilling firms with the result the F-cal value as 344.632 while F tabulated value as 3.901 leading to rejection of hull hypothesis. Based on the findings, it was the recommended that oil drilling firms should strengthen their inventory management system for effective and timely work delivery in order to avert downtime, loss of income and termination of contracts. Finally, members of staff of an oil and gas drilling firms in inventory unit should be trained and retrained on regular basis to embrace technological changes in inventory management to improve their performances which would in turn strengthen the inventory management of such firms.